2015
DOI: 10.1242/dmm.021394
|View full text |Cite
|
Sign up to set email alerts
|

CLARITY and PACT-based imaging of adult zebrafish and mouse for whole-animal analysis of infections

Abstract: Visualization of infection and the associated host response has been challenging in adult vertebrates. Owing to their transparency, zebrafish larvae have been used to directly observe infection in vivo; however, such larvae have not yet developed a functional adaptive immune system. Cells involved in adaptive immunity mature later and have therefore been difficult to access optically in intact animals. Thus, the study of many aspects of vertebrate infection requires dissection of adult organs or ex vivo isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…CLARITY processing followed by E-cadherin staining demonstrated that individual granulomas were isolated cleanly and were not disrupted during dissection (Chung et al, 2013; Cronan et al, 2015; Yang et al, 2014). Isolated granulomas had central necrotic foci replete with bacteria surrounded by intact layers of E-cadherin-positive cells (Figure 4D), in agreement with findings in tissue sections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CLARITY processing followed by E-cadherin staining demonstrated that individual granulomas were isolated cleanly and were not disrupted during dissection (Chung et al, 2013; Cronan et al, 2015; Yang et al, 2014). Isolated granulomas had central necrotic foci replete with bacteria surrounded by intact layers of E-cadherin-positive cells (Figure 4D), in agreement with findings in tissue sections.…”
Section: Resultsmentioning
confidence: 99%
“…To better assess the morphological transformations within the granuloma, we used CLARITY to clear dissected zebrafish organs (Figure 5K) (Chung et al, 2013; Cronan et al, 2015; Yang et al, 2014). In control (Tg(mfap4:icre; ubb:BSR); Gt(jup-citrine) ct520a ) animals, the bacteria-laden core of the granuloma was surrounded by adherens junctions (Figure 5L, Movie S3).…”
Section: Resultsmentioning
confidence: 99%
“…The founder of this family of methods is CLARITY (Chung et al, 2013; Tomer et al, 2014; Ye et al, 2016), which has been modified by other labs to yield, among others, PACT-PARS (which reduces cost and increases speed of clearing using constant perfusion (Treweek et al, 2015)), ACT (which speeds up clearing with custom electrophoresis equipment (Lee et al, 2016)), and SWITCH (which accelerates clearing using high temperatures (Murray et al, 2015)). These methods have been applied successfully to map brain-wide activity and neural projections (CLARITY (Ye et al, 2016)), visualize Mycobacterium tuberculosis infections deep in whole lungs (PACT (Cronan et al, 2015)), and can even be used to clear bones (PACT-deCAL (Treweek et al, 2015)).…”
Section: How Do I Decide Which Tissue Clearing Methods Is Optimal For mentioning
confidence: 99%
“…Advances in optical clearing of whole zebrafish for 3-dimensional in situ analysis of granulomas is a powerful tool for relatively artifact-free microscopy but requires access to expensive multiphoton microscopes to access deep tissues (Cronan et al, 2015). Our method attempts to census the granuloma load of individual zebrafish by creating a catalog of thin section snapshots at 200 μm intervals providing confidence that granulomas are not double counted.…”
Section: Discussionmentioning
confidence: 99%